Legal regulation of social security principles in the countries of the European Union and Ukraine - Bohdan Torokhtii; Larysa Nalyvaiko; Volodymyr Horbalinskyi; Nataliia Obushenko; Oleg Bolgar (Nusantara: Journal of Law Studies, 2026)
The purpose of the article is a comprehensive analysis of the legal regulation of social security principles in the countries of the European Union and Ukraine. The application of the comparative law method can serve as an analysis of the principle of solidarity in the social security systems of Ukraine and the European Union. In Germany, the social insurance system is built on mandatory contributions from employees and employers with a clearly defined balance of responsibility of the parties. In France, along with the insurance principle, state budget financing plays a significant role, which strengthens the guarantee nature of social payments. In Ukraine, the principle of solidarity is also enshrined at the legislative level, but its implementation is complicated by demographic factors and the deficit of the Pension Fund. Comparative analysis allows us to establish that the effectiveness of the implementation of the principle of solidarity depends not only on regulatory consolidation, but also on the stability of the financial and economic system of the state. The normative sources that define the fundamental principles of social protection, in particular the principles of solidarity, universality, subsidiarity, equality and non-discrimination, are studied. The influence of European Union law on the formation of national models of social security is considered, as well as the prospects for harmonizing Ukrainian legislation in the context of European integration processes. Directions for improving Ukrainian legislation taking into account European standards are proposed. Ukrainian legislation contains the basic principles of social security, but requires further systematization and harmonization with European standards.